The Question of Minorities in Islam : Theorical Prespectives and Case Studies - Mohammed El-Tahir El-Mesawi (The Other Press, 2015)
Difference, diversity and variation among human beings, both as individuals and groups, and hence, the presence of the different other ogether with she self have always been one of the main expressions and ramifications of the original identity and essential unity of the human species.